The Role of Optimal Nutrition in Supporting the Immune System A Literature Review - Yuli Sleven (Journal of Nutrition and Health Care, 2024)
This article aims to explore the role of optimal nutrition in supporting the immune system, through an extensive literature analysis. By focusing on essential nutrients, intestinal microbiota interactions, and the impact of nutritional deficiencies, we describe how these aspects contribute to the effectiveness of the immune response. Literature results show that optimal intake of vitamin C, vitamin D, zinc, and selenium plays a crucial role in increasing the activity of immune cells and stimulating inflammatory responses. In addition, the balance of intestinal microbiota, which can be improved through the consumption of probiotics, has been shown to support the body's resistance to infection. On the other hand, nutritional deficiencies can inhibit immune system function, increasing susceptibility to disease. Integrating nutrition into your daily diet, especially through increasing consumption of fruit and vegetables, is a practical strategy for increasing the body's endurance. In conclusion, a deep understanding of the relationship between nutrition and immunity provides a basis for the development of effective nutritional strategies in improving health and the body's response to disease. This article invites readers to consider the important role of nutrition in the context of disease prevention and holistic health maintenance.